2018
DOI: 10.17977/um002v10i12018p103
|View full text |Cite
|
Sign up to set email alerts
|

Economics of Small-scale Sheep Marketing in Gombe Metropolitan Livestock Markets Gombe State, Nigeria

Abstract: This paper assessed the profitability of small-scale sheep marketing in Gombe Metropolis. Four sheep markets were purposively selected for their popularity in small ruminants marketing. A multi-stage sampling technique was used to select 91 sheep marketers these markets. Data were collected using structured questionnaire and were analysed using descriptive statistics, farm budget and maximisation of consumer satisfaction models. The result revealed that purchasing cost for ram and ewe constituted 92.59% and 91… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Based on the data above, it can be concluded that the farmer's share received by Sentra Ternak Dompet Dhuafa in Deli Serdang Regency is high because all marketing channels obtain a farmer's share value above> 50%. This is in accordance with the [12] which states that farmer's share is said to be efficient if the value is < 50%, and inefficient if it is > 50%. The value of farmer's share is influenced by the length of the marketing channel and the amount of selling price to consumers.…”
Section: Advantages Of Marketing Institutionssupporting
confidence: 87%
“…Based on the data above, it can be concluded that the farmer's share received by Sentra Ternak Dompet Dhuafa in Deli Serdang Regency is high because all marketing channels obtain a farmer's share value above> 50%. This is in accordance with the [12] which states that farmer's share is said to be efficient if the value is < 50%, and inefficient if it is > 50%. The value of farmer's share is influenced by the length of the marketing channel and the amount of selling price to consumers.…”
Section: Advantages Of Marketing Institutionssupporting
confidence: 87%
“…In most African countries such as Benin, animals are often sold live in livestock markets through different marketing channels involving multiple actors at different levels (Kocho et al 2011;Abdullahi et al 2018). In this study, four marketing channels were identified in the beef cattle markets selected.…”
Section: Discussionmentioning
confidence: 99%
“…These channels include market participants such as beef cattle farmers, collectors, wholesalers, retailers (slaughterhouse/butcheries). In the beef cattle markets in the area studied, animals are generally traded by "eye-ball" pricing on a per-head basis, and agreements between seller and buyer are reached after negotiations sometimes involving commissioners (brokers) (Kocho et al 2011;Pratama and Supranianondo 2017;Abdullahi et al 2018). Animal prices are higher in the MBA markets than in the MT markets (Onibon 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marketing efficiency is the ratio between marketing costs and selling prices to consumers. Quantifies the value of marketing channel efficiency as follows Eps= TB X100% TNP Information: Eps : Marketing efficiency (%) TB : Total marketing costs (Rp) TNP: Total product value (Rp) Decision rule: Eps > 50% = Inefficient Eps < 50 % = Efficient 2.5 Marketing margin [3,4] marketing margin as the difference between the price that final consumers pay and the price that farmers and producers receive. The marketing margin encompasses both marketing costs and marketing profits within the context of marketing expenses.…”
Section: Marketing Efficiencymentioning
confidence: 99%